2020
DOI: 10.3390/ijerph17249266
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of Gambling Predictors among Adolescents

Abstract: Although gambling is forbidden for minors, the prevalence of gambling among adolescents is increasing. In order to improve preventive interventions, more evidence on predictors of gambling onset is needed. A longitudinal study was proposed to (1) establish the prevalence of gambling; (2) identify factors associated with gambling behavior the following year; and (3) adjust a model to predict gambling behavior. A cohort of 1074 students (13–18 years old) was followed for 12 months. The prevalence of gambling rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 82 publications
3
13
0
1
Order By: Relevance
“…Consistent with the findings of previous studies that assess perceived gambling availability in both offline and online venues (Botella-Guijarro et al, 2020) and with those Fig. 2 Regression slopes for perceived gambling availability (at baseline) on problem gambling (at followup) at low, moderate, and high levels of self-efficacy to control gambling (at baseline) that only measured perceived availability of offline facilities (Gavriel-Fried et al, 2021;Wickwire, et al, 2007), our results suggest that perceived availability is a risk factor for gambling frequency.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with the findings of previous studies that assess perceived gambling availability in both offline and online venues (Botella-Guijarro et al, 2020) and with those Fig. 2 Regression slopes for perceived gambling availability (at baseline) on problem gambling (at followup) at low, moderate, and high levels of self-efficacy to control gambling (at baseline) that only measured perceived availability of offline facilities (Gavriel-Fried et al, 2021;Wickwire, et al, 2007), our results suggest that perceived availability is a risk factor for gambling frequency.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that the first gambling experiences usually occur offline (Kang et al, 2020;Törrönen et al, 2020). This could explain why our results are consistent with previous studies showing an association between perceived gambling availability and gambling frequency, regardless of whether these studies measure online (Botella-Guijarro et al, 2020) and/or offline gambling (Wickwire et al, 2007). However, with regard to problem gambling, our results are inconsistent with those of Wickwire et al (2007), who did not find a relationship between perceived gambling availability and gambling-related problems.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations